TCP Transcription Factors in Moso Bamboo (Phyllostachys edulis): Genome-Wide Identification and Expression Analysis - Liu, Huan-Long; Wu, Min; Li, Fei; Gao, Ya-Meng; Chen, Feng; Xiang, Yan (Frontiers in Plant Science, 2018)
TEOSINTE BRANCHED 1, CYCLOIDEA, and PROLIFERATING CELL FACTORS (T), members of a plant-specific gene family, play significant roles during plant growth and development, as well as in response to environmental stress. However, knowledge about this family in moso bamboo (Phyllostachys edulis) is limited. Therefore, in this study, the first genome-wide identification, classification, characterization, and expression pattern analysis of the TCP transcription factor family in moso bamboo was performed. Sixteen TCP members were identified from the moso bamboo genome using a BLASTP algorithm-based method and verified using the Pfam database. Based on a multiple-sequence alignment, the members were divided into two subfamilies, and members of the same family shared highly conserved motif structures. Subcellular localization and transactivation activity analyses of four selected genes revealed that they were nuclear localized and had self-activation activities. Additionally, the expression levels of several PeTCP members were significantly upregulated under abscisic acid, methyl jasmonate, and salicylic acid treatments, indicating that they play crucial plant hormone transduction roles in the processes of plant growth and development, as well as in responses to environmental stresses. Thus, the current study provides previously lacking information on the TCP family in moso bamboo and reveals the potential functions of this gene family in growth and development.